2020
DOI: 10.1016/j.ajhg.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Allelic UQCRFS1 Variants Are Associated with Mitochondrial Complex III Deficiency, Cardiomyopathy, and Alopecia Totalis

Abstract: Isolated complex III (CIII) deficiencies are among the least frequently diagnosed mitochondrial disorders. Clinical symptoms range from isolated myopathy to severe multi-systemic disorders with early death and disability. To date, we know of pathogenic variants in genes encoding five out of 10 subunits and five out of 13 assembly factors of CIII. Here we describe rare bi-allelic variants in the gene of a catalytic subunit of CIII, UQCRFS1, which encodes the Rieske iron-sulfur protein, in two unrelated individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In the case of CYC1, two different missense mutations were present in two unrelated individuals showing a similar clinical course with cIII deficiency accompanied by recurrent metabolic crises and insulinresponsive hyperglycemia [159]. Defective UQCRFS1 has been deemed the cause of decreased cIII activity, lactic acidosis, cardiomyopathy, and alopecia totalis [160].…”
Section: Mutations In Complex III Structural Subunitsmentioning
confidence: 99%
“…In the case of CYC1, two different missense mutations were present in two unrelated individuals showing a similar clinical course with cIII deficiency accompanied by recurrent metabolic crises and insulinresponsive hyperglycemia [159]. Defective UQCRFS1 has been deemed the cause of decreased cIII activity, lactic acidosis, cardiomyopathy, and alopecia totalis [160].…”
Section: Mutations In Complex III Structural Subunitsmentioning
confidence: 99%
“… 31 Rare mutations in UQCRFS1 have been previously reported as the cause of a mitochondrial disorder (MIM: 618775). 32 Further, Uqcrfs1 deletion in mice abolishes mitochondrial reactive oxygen species that are required for antigen specific T cell responses, a hallmark of the adaptive immune response. 33 We did not observe replication of rs148218440 in BioVU non-MEGA EX AA ( Table 1 ), however we note that this analysis was underpowered to detect effect (n = 292 affected individuals and 1,145 control individuals, Table S4 ); UK Biobank did not have enough AA individuals with pneumonia to perform a replication analysis (n = 76 affected individuals and 9,272 control individuals, Table S5 ).…”
Section: Main Textmentioning
confidence: 99%
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [ 37 ], RBM3 [ 38 ], BAK1 [ 39 ], NDUFC2 [ 40 ], NDUFS4 [ 41 ], NDUFS5 [ 42 ], UQCRFS1 [ 43 ], COX6B1 [ 44 ], NDUFA13 [ 45 ], PRMT1 [ 46 ], RDX (radixin) [ 47 ], EPHB4 [ 48 ], SYNE2 [ 49 ], DNAH5 [ 50 ], NEDD4L [ 51 ], PDE4B [ 52 ] and CTNND1 [ 53 ] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [ 54 ], Zi et al [ 55 ], Kunej et al [ 56 ], Van der Schueren et al [ 57 ], Jin et al [ 58 ], Emdad et al [ 59 ], Liu et al [ 60 ], Scherag et al [ 61 ], Shi and Long [ 62 ], Sharma et al [ 63 ], Parente et al [ 64 ], Saint-Laurent et al [ 65 ] and Lee [ 66 ] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%